1979
DOI: 10.1128/aac.16.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of agrocin 84

Abstract: A procedure for the rapid purification of milligram quantities of agrocin 84, a bacteriocin-like compound produced by Agrobacterium radiobacter strain K-84, has been developed. This procedure, which employs charcoal adsorption, ion-exchange, sieving chromatography, and continuous-flow electrophoresis, can yield agrocin 84 which is 65% pure on a dry weight basis. The purest preparations were strongly ultraviolet absorbing, with a maximum at 264 nm (epsilon 7.0/264 = 22,675 cm2 - M-1) and a minimum at 227 nm (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…[4,10] Moreover, recent NMR studies showed the presence of galactofuranosyl residues with the opposite α-configuration, in Leishmania, [6] Penicillium [11] or Clostridium [12] species. In contrast to the galacto-conjugates, the nucleotide-sugar Agrocine 84, [13,14] a natural antibiotic that controls the plant cancer crown disease, [13] is notably characterized by a glucofuranose moiety whose anomeric configuration has not yet been clearly determined. Since the biosynthesis of glycoconjugates containing hexofuranosides seems to be restricted to lower organisms, it is assumed that compounds bearing such units could be strongly antigenic [4] and may be useful targets for therapy in fungal and parasitic diseases.…”
mentioning
confidence: 97%
“…[4,10] Moreover, recent NMR studies showed the presence of galactofuranosyl residues with the opposite α-configuration, in Leishmania, [6] Penicillium [11] or Clostridium [12] species. In contrast to the galacto-conjugates, the nucleotide-sugar Agrocine 84, [13,14] a natural antibiotic that controls the plant cancer crown disease, [13] is notably characterized by a glucofuranose moiety whose anomeric configuration has not yet been clearly determined. Since the biosynthesis of glycoconjugates containing hexofuranosides seems to be restricted to lower organisms, it is assumed that compounds bearing such units could be strongly antigenic [4] and may be useful targets for therapy in fungal and parasitic diseases.…”
mentioning
confidence: 97%
“…Rather, it probably is not a protein, and its molecular weight is similar to that of agrocin 84, a bacteriocin of Agrobacterium radiobacter K84 that inhibits the growth of Agrobacterium turnefaciens. Agrocin 84 is an adenine nucleotide analog with a molecular weight of 1,350 (12). However, small differs from agrocin 84 in at least two respects.…”
Section: Discussionmentioning
confidence: 99%
“…radiobacter strain K84 (producer of the bacteriocin, agrocin 84), against A. radiobacter pv. tumefaciens, the cause of crown-gall disease (18,19). Application of a mutant strain which was unable to produce agrocin 84 and still reduced disease symptoms indicated that, possibly, competition with the pathogen on the host receptor site was also important (20).…”
Section: Bacterial Antibioticsmentioning
confidence: 98%